El aura en el streaming cinematográfico (Monográficos) - Montenegro Sandoval, Daniel A. (2022)
The arrival of streaming platforms marked a turning point in cinema consumption mechanisms because of the flexibility of the time-space factor. It becomes customary. However, this relationship has also been deformed as the publics conscience relocated itself. Therefore, it is likely that this new system is organic to creative processes and their reception by viewers mediated by technological devices. The present work aims to locate the new place that time and space occupy in the relationship between cinema and its audience and the presence of the aura in this transaction. To do this, a brief review of the subject-spectator will be made in the face of cinematographic practices and the codes that allow, or not, to overcome the limits of the here and now suggested by Walter Benjamin in his text “The work of art in the time of mechanical reproduction”.